Izin lingkungan dalam sistem OSS sebagai sarana kemudahan pengawasan perizinan berusaha - Fadlan, Mochamad Lailul (Maliki Interdisciplinary Journal, 2024)
The implementation and issuance of PP Number 24 of 2018 concerning Electronically Integrated Business Licensing Services, which is a development of the One-Stop Service, has created confusion for business actors regarding the environmental licensing system that must be carried out and adhered to in running their business. The aim of this research is to find out about Environmental Permit Regulations and Environmental Impact Analysis (AMDAL) in the Online Single Submission (OSS) System in supervising permits for doing business in Indonesia. The research method uses a normative juridical research type, with a statutory approach. Data collection is carried out by collecting written data related to the problem being studied. The results of the discussion are presented descriptively. The results of the discussion show that in PP Number 24 of 2018 concerning Electronically Integrated Business Licensing Services it is determined that business actors are required to provide environmental permit commitments issued by the authorized body, namely the OSS body by completing the required documents, namely UKL- UPL and AMDAL documents. The AMDAL document consists of ANDAL, RPL, and RKL. Business actors are required to complete the requirements that have been determined in processing business permit commitments, including: IMB, Certificate of Functional Appropriateness, Environmental Impact Analysis, UKL-UPL, and SPPL (Letter of Statement of Capability for Environmental Management and Monitoring).